Bilateral agreement for the academic year 2012/2014 LLP programme: higher education (Erasmus) between Universidade Lusíada de Lisboa and Università del Salento - Universidade Lusíada de Lisboa (2016)
- Cooperate for exchange of students and/or staff in the context of the Erasmus programme; - Subject area: Political sciences and civics.